Data structures & other objects : - Main, Michael (Addison Wesley, 2003)
Michael Main's gentle approach to data structures and objects has introduced thousands of beginning programmers to foundational data structures using the practical Java language. This Edition makes the most of the enhancements and advantages of Java 5.0 including the use of generic data types. An early group of chapters reviews the key aspects of object-oriented programming giving students the foundation for understanding significant programming concepts. With this framework they are able to accomplish writing functional data structures by using a five-step method for working with data types; understanding the data type abstractly, writing a specification, using the data type, designing and implementing the data type, and analyzing the implementation. Students learn to think analytically about the efficiency and efficacy of design while gaining exposure to useful Java classes libraries. The flexibility of Data Structures and Other Objects Using Java allows instructors to structure their course around a certain emphasis, such as early coverage of recursion and sorting, or to accelerate the pace of the course.